A Novel Mutation of GFAP Causing Adult-Onset Alexander Disease - Ciammola, Andrea; Sangalli, Davide; Sassone, Jenny; Poletti, Barbara; Carelli, Laura; Banfi, Paolo; Pappacoda, Gabriele; Ceccherini, Isabella; Grossi, Alice; Maderna, Luca; Pingue, Monica; Girotti, Floriano; et al. (Frontiers in Neurology, 2019)
Alexander disease (AxD) is a rare, autosomal dominant neurological disorder. Three clinical subtypes are distinguished based on age at onset: infantile (0-2 years), juvenile (2-13 years), and adult (>13 years). The three forms differ in symptoms and prognosis. Rapid neurological decline with a fatal course characterizes the early-onset forms, while symptoms are milder and survival is longer in the adult forms. Currently, the sole known cause of AxD is mutations in the GFAP gene, which encodes a type III intermediate filament protein that is predominantly expressed in astrocytes. A wide spectrum of GFAP mutations comprising point mutations, small insertions, and deletions is associated with the disease. The genotype-phenotype correlation remains unclear. The considerable heterogeneity in severity of disease among individuals carrying identical mutations suggests that other genetic or environmental factors probably modify age at onset or progression of AxD. Describing new cases is therefore important for establishing reliable genotype-phenotype correlations and revealing environmental factors able to modify age at onset or progression of AxD. We report the case of a 54-year-old Caucasian woman, previously diagnosed with ovarian cancer and treated with surgery and chemotherapy, who developed dysarthria, ataxia, and spastic tetraparesis involving mainly the left side. Cerebral and spinal magnetic resonance imaging (MRI) revealed a peculiar tadpole-like atrophy of the brainstem. Genetic analysis of the GFAP gene detected a heterozygous mutation in exon 1 (c.219G>C), resulting in an amino acid exchange from methionine to isoleucine at codon 73 (p.M73I). The expression of this mutant in vitro affected the formation of the intermediate filament network. Thus, we have identified a new GFAP mutation in a patient with an adult form of AxD.